Detailed Analysis of Diffuse Large B Cell Lymphoma Patients: A Single-Center, Retrospective Study. (30th July 2013) - Ozbalak, Murat; Ar, M. Cem; Tuzuner, Nukhet; Salihoglu, Ayse; Eskazan, A. Emre; Ongoren Aydin, Seniz; Baslar, Zafer; Soysal, Teoman; Aydin, Yildiz; Barak Dolgun, Anil; Ergonul, Onder; Ferhanoglu, Burhan
Abstract : The aim of this single-center, retrospective study was to investigate the impact of rituximab, reconsider the validity of International Prognostic Index (IPI), and evaluate the prognostic role of the cell of origin (CoO) in a relatively young cohort. Three hundred twelve diffuse large B cell lymphoma patients (median age: 52) were included. Rituximab significantly improved the 3- and 5-year progression free survival (PFS) (70% versus 65% and 41% versus 36%, resp.; P < 0.001 ) but led only to a slight, insignificant increase in 3- and 5-year overall survival (OS) (71% versus 77.3% and %67 versus 74.5%, resp.; P = 0.264 ). In the young, low risk patient subgroup (aaIPI = 0&1; n = 129 ), rituximab improved 3- and 5-year PFS and OS rates (P < 0.001 and P = 0.048, resp.). The efficacy of rituximab in young high risk patients was comparable to the literature. CoO data were available in 190 patients. The OS at 3 years was 79% for GC and 64% for non-GC subgroups (P = 0.014 ). To the best of our knowledge, this is the first study which investigated the impact of R-CHOP in the context of CoO and IPI in a relatively young cohort. CoO was not an independent risk factor for prognosis in the multivariate analysis although patients with GC showed a significant survival advantage in the univariate analysis. CoO was also found to be a significant determinant of response in refractory/relapsed patients. Our results confirm the efficacy of rituximab in low and high risk, young patients outside of a randomized clinical trial setting.